Managing Web-based Information Resources Under Uncertainty: A Probabilistic Approach - Omri, Asma; Omri, Mohamed-Nazih (Journal of Web Engineering, 2024)
“Uncertainty” is related to working with inaccurate data, imprecise and incomplete information, and unreliable results that can lead to irrational decisions. Several approaches to managing uncertain data on the Web have been proposed in the literature to resolve this problem. These approaches have failed to find the solution to this problem with accuracy and performance. Our study aims to propose a new probabilistic approach to manage Web information resources in an uncertain large-scale cloud environment. Our approach is based on three main steps: (1) modelling uncertain Web resources, (2) computing HTTP request model, and (3) interpretation and evaluation of uncertain Web resources in a context of classic hypertext navigation. The experimental study shows that the analysis of the execution time necessary for the composition of the services, by our approach, is negligible, compared to that of the other studied approaches. The algorithm that deals with the impact of the variation in the number of nodes, which we have proposed, has also been evaluated and checks all the possibilities in polynomial time and can adapt to many possibilities of multiplexing of values.